2019
DOI: 10.1111/jdv.15423
|View full text |Cite
|
Sign up to set email alerts
|

Crossed looks on the dermatologist's position and the patient's preoccupations as to psoriasis and pregnancy: preliminary results of the PREGNAN‐PSO study

Abstract: Background While some information on psoriasis impact on pregnancy is available, very little is known on the preoccupations of women afflicted by the disease or on the dermatologists' (D) positioning as to psoriasis and pregnancy. The 'Objectifs Peau' project demonstrated a 4.7% prevalence of psoriasis in women aged 18-45 years in France.Objective This project sought to further address these issues in view of a targeted action plan.Methods A questionnaire was made available to 361 D of different types. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…We previously reported on the difficulties of opening up and discussing sexuality with physicians. 2 In a study of 183 couples, we found that psoriasis severity and/or a significant impact on QoL were factors associated with sexual dysfunction in male partners of women with psoriasis, but the opposite scenario was not observed. 7 Contraception in childbearing women with psoriasis is important, and therapeutic options must be considered for all women with psoriasis who are sexually active irrespective of intentions of starting a family.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…We previously reported on the difficulties of opening up and discussing sexuality with physicians. 2 In a study of 183 couples, we found that psoriasis severity and/or a significant impact on QoL were factors associated with sexual dysfunction in male partners of women with psoriasis, but the opposite scenario was not observed. 7 Contraception in childbearing women with psoriasis is important, and therapeutic options must be considered for all women with psoriasis who are sexually active irrespective of intentions of starting a family.…”
Section: Discussionmentioning
confidence: 90%
“…In our previous study, dermatologists reported, that upon diagnosing women of childbearing age with psoriasis, they approached short-term desires of pregnancy (83.5%), contraception (68%), long-term desires of pregnancy (41%) and drug therapies during pregnancy (35%). 2 Conversely, according to dermatologists, the main topics discussed by women included compatibility of therapy with pregnancy (64%), disease transmission (54%), foetal risks of therapy (49%), and contraception (32%). 2 However, in the present study, 13-14% of nonpregnant women reported that the physician managing their psoriasis discussed child planning and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor, We recently read with interest the results published by Maccari et al 1 in 'Crossed looks on the dermatologist's position and the patient's preoccupations as to psoriasis and pregnancy: preliminary results of the PREGNAN-PSO study'. This study sheds light on knowledge gaps in a cohort of dermatologists' understanding on treatment of psoriasis in pregnancy.…”
Section: Use Of Biologics In Pregnancy: Limitations Stemming From CLImentioning
confidence: 99%